Modelling the anisotropic inelastic response of polymeric scaffolds for in situ tissue engineering applications - Terzano, Michele; Wollner, Maximilian P.; Kainz, Manuel P.; Rolf-Pissarczyk, Malte; Götzen, Nils; Holzapfel, Gerhard A. (Journal of the Royal Society Interface, 2023)
In situ tissue engineering offers an innovative solution for replacement valves and grafts in cardiovascular medicine. In this approach, a scaffold, which can be obtained by polymer electrospinning, is implanted into the human body and then infiltrated by cells, eventually replacing the scaffold with native tissue. In silico simulations of the whole process in patient-specific models, including implantation, growth and degradation, are very attractive to study the factors that might influence the end result. In our research, we focused on the mechanical behaviour of the polymeric scaffold and its short-term response. Following a recently proposed constitutive model for the anisotropic inelastic behaviour of fibrous polymeric materials, we present here its numerical implementation in a finite element framework. The numerical model is developed as user material for commercial finite element software. The verification of the implementation is performed for elementary deformations. Furthermore, a parallel-plate test is proposed as a large-scale representative example, and the model is validated by comparison with experiments.
Created from Fastlane, Scopus look-up
Keywords: anisotropy; electrospinning; endogenous tissue restoration; tissue engineering; viscoelasticity